Pemodelan dan Rekomendasi Proses Bisnis menggunakan Metode Business Process Improvement (BPI) (Studi Kasus CV Wisa Tunggal Perkasa) - Muhammad Tri Hermawan; Buce Trias Hanggara; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
CV. Wisa Tunggal Perkasa is engaged in selling building materials. The author found several processes carried out accordingly so that the process occurs the process becomes obstructed or less effective. Indications that occur in the process of selling goods and purchasing goods. This indication is that there is no inventory calculation and there is no re-recording of goods from suppliers. Based on the allegations, researchers will discuss business processes and analyze potential problems and analysis of problems that occur and then will evaluate business processes on the CV. Wisa Tunggal Perkasa. This study uses a Bussiness Process Model and Notation (BPMN), while for analyzing and evaluating using the Failure Mode and Effect Analysis (FMEA) method and for conducting business improvement processes using Business Process Improvement (BPI). From the results of simulations of the current business process (as-is) and the business evaluation process (to-be) found when the analysis reached 33.22% in the sale of goods and 24.66% in the purchase of goods. In addition, the analysis of resources with the highest increase was 46.44% in the business process of selling goods carried out by cashier actors and 58.98% by owners in the business process of purchasing goods.